2011
DOI: 10.1371/journal.pone.0018810
|View full text |Cite
|
Sign up to set email alerts
|

Response of Estrogen Receptor-Positive Breast Cancer Tumorspheres to Antiestrogen Treatments

Abstract: Estrogen signaling plays a critical role in the pathogenesis of breast cancer. Because the majority of breast carcinomas express the estrogen receptor ERα, endocrine therapy that impedes estrogen-ER signaling reduces breast cancer mortality and has become a mainstay of breast cancer treatment. However, patients remain at continued risk of relapse for many years after endocrine treatment. It has been proposed that cancer recurrence may be attributed to cancer stem cells (CSCs)/tumor-initiating cells (TICs). Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…This assay is used as a stem-like functional assay that allows the propagation of mammary epithelial and breast tumour cells in an undifferentiated state based on their ability to proliferate in suspension (Dontu et al, 2003;Ponti et al, 2005;Farnie et al, 2007) and has been used for cancer stem-like specific drug screening in MCF7 cells (Zhou et al, 2007;Ao et al, 2011). We did observe induction of Sox2 expression in mammospheres obtained from human breast tumour cell cultures, and from MCF7 and T47D cells.…”
Section: Sox2 Activation In Breast Cancer Stem Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…This assay is used as a stem-like functional assay that allows the propagation of mammary epithelial and breast tumour cells in an undifferentiated state based on their ability to proliferate in suspension (Dontu et al, 2003;Ponti et al, 2005;Farnie et al, 2007) and has been used for cancer stem-like specific drug screening in MCF7 cells (Zhou et al, 2007;Ao et al, 2011). We did observe induction of Sox2 expression in mammospheres obtained from human breast tumour cell cultures, and from MCF7 and T47D cells.…”
Section: Sox2 Activation In Breast Cancer Stem Cellsmentioning
confidence: 81%
“…We therefore examined the ability of MCF7 breast carcinoma cells to grow as tumour spheres, measuring the ability to form mammospheres in serial passages and to make clonal spheres from single cells, reflecting the stem cell-like properties of selfrenewal and asymmetric division ( Figure 2a). Indeed, the mammosphere assay has been demonstrated in MCF7 cells to enrich and propagate cells with enhanced tumour-initiating ability (Ao et al, 2011). We used a commercial antibody array that allows assessing the expression of Oct4, Sox2, Nanog, and other (Figure 2d).…”
Section: Sox2 Activation In Breast Cancer Stem Cellsmentioning
confidence: 99%
“…The urage of tamoxifen as positive control is a estrogen receptor α partial agonis, was regarded as first line drug in ER-α over expressed breast cancer treatment (Ao et al, 2011;Fowler et al, 2004). Tamoxifen, was also tested against MCF-7 cells by the same procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The same results were true for suspension cultures of primary human normal and tumor breast cell suspensions, where treatment with 4-OH-tamoxifen led to an increase in Nanog and Sox-2. Ao et al [32] on the other hand treated suspension cultures with 4-OH-tamoxifen and then passaged the cells to media without antiestrogen (still in suspension) and found that under these conditions a greater amount of mammospheres were formed. We showed that tamoxifen selects for cells with stem cell properties in the human MCF-7 cells line, as well as in mouse LM05-E cells and the M05 tumor from which they derive [33] .…”
Section: Resistancementioning
confidence: 99%